2015
DOI: 10.3329/brj.v19i1.25214
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence of Balam Rice (Oryza sativa L.) Germplasm of Bangladesh

Abstract: Forty genotypes of Balam rice germplasm of Bangladesh were studied for 17 morphophysicochemical characters at BRRI during 2009-11. The cluster analysis using Mahalanobis' D 2 statistics, grouped the genotypes into seven clusters, where no duplicate germplasm was found for the studied characters. The highest number of genotypes (8) was constellated into clusters I, III and V and the lowest (2) was in cluster IV. The intraand inter-cluster distances were maximum (1.17 and 21.16) in cluster VII and between cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
(23 reference statements)
5
5
0
Order By: Relevance
“…The result exposed that the first five components in the PCA with Eigen values >1.0, contributed 81.14% of the total variations among the genotypes for 15 morphological characters. These results are in agreement with the findings of Ahmed et al (2015b). Fig.…”
Section: Grain Traitssupporting
confidence: 93%
See 1 more Smart Citation
“…The result exposed that the first five components in the PCA with Eigen values >1.0, contributed 81.14% of the total variations among the genotypes for 15 morphological characters. These results are in agreement with the findings of Ahmed et al (2015b). Fig.…”
Section: Grain Traitssupporting
confidence: 93%
“…The inter-cluster distances in all the clusters were higher than the intra-cluster distances suggesting wider genetic diversity among the genotype of different groups. The results were in agreement with Islam et al (2016), Akter et al (2016), Ahmed et al (2015b), Islam et al (2014) and Sohrabi et al (2012). Table 7 presents the cluster-mean values for all the 15 quantitative characters.…”
Section: Quantitative Traits Characterizationsupporting
confidence: 87%
“…On the other hand, the inter cluster distances in all the clusters were higher than the intra cluster distances suggesting wider genetic diversity among the landraces of different groups. The results were in agreement with Siddique et al (2013) and Ahmed et al (2015). Again, Islam et al (2016) reported intra and inter-cluster distance ranged from 0.61 to 1.27 and 3.71 to 16.12, respectively on aromatic and fine rice genotypes.…”
Section: Quantitative Traits Characterizationsupporting
confidence: 87%
“…The cluster mean revealed that the crosses between the genotypes of cluster I with those of clusters II and IV would exhibit high heterosis for maximum good characters. Ahmed et al (2015) and Sohrabi et al (2012) earlier reported similar trend of conclusions on rice germplasm using D 2 statistic Table 8 presents contributions of the characters towards divergence. The canonical vector analysis revealed that the vectors (vector I and II) were positive for yield, grain breadth, days to flowering, days to maturity, culm diameter, ligule length.…”
Section: Quantitative Traits Characterizationsupporting
confidence: 58%
“…Where, X 1 -Days to 50 per cent flowering X 6 -Number of spikelets per panicle X 11 -Harvest index (%) X 2 -Days to maturity X 7 -Number of filled grains per panicle X 12 -1000 grain weight (g) X 3 -Plant height (cm) X 8 -Panicle length (cm) X 13 -Absolute growth rate (mg/day/plant) X 4 -Number of tillers per plant X 9 -Grain yield per plant (g) X 5 -Number of productive tillers per plant X 10 -Straw yield per plant (g) The maximum inter cluster distance indicates the wider genetic diversity among the genotypes falling into the groups which can be utilized in hybridization programs while the minimum inter cluster distance indicates that the genotypes falling in such clusters are closely related and thus hybridization among such genotypes will not give any fruitful result. The greater distance between the two clusters indicates the wider genetic diversity between the genotypes (Ahmed et al, 2015). Hence it is desirable to select genotypes from the clusters showing high inter cluster distance coupled with high grain yield as parents in future breeding programs for developing varieties and hybrids with wider variability and desirable quality for submergence tolerance.…”
Section: Resultsmentioning
confidence: 99%